2019
DOI: 10.3389/fmicb.2019.00967
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Establishment in Agricultural Soil and Colonization of Crop Plants Depend on Soil Type and Plant Species

Abstract: Human pathogenic bacteria, such as Salmonella enterica , are able to colonize crop plants. So far, not much is known about biotic and abiotic factors influencing this colonization in field soil. This understanding, however, is imperative for the provision of safe fresh produce to the consumer. In this study, we investigated the effects of soil type, organic fertilization, plant species and the way of Salmonella entry into the plant production system, on the surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
117
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(129 citation statements)
references
References 67 publications
4
117
2
6
Order By: Relevance
“…For example, the survival of Listeria monocytogenes in soil depends on the acidity and the present microbiota (Locatelli et al, 2013). The soil type, root exudates and organic fertilizer might also influence the persistence of pathogens in soil (Berg and Smalla, 2009;Locatelli et al, 2013;Schlaeppi et al, 2014;Jechalke et al, 2019). However, the relationship between the biotic diversity and biotic resistance towards invading organisms, is not fully understood; it seems that environments with high biological diversity have narrower niches and/or might have a higher chance to harbour natural antagonists and competitors (Chapin III et al, 2000;Loreau and Hector, 2001;Mallon et al, 2015;Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the survival of Listeria monocytogenes in soil depends on the acidity and the present microbiota (Locatelli et al, 2013). The soil type, root exudates and organic fertilizer might also influence the persistence of pathogens in soil (Berg and Smalla, 2009;Locatelli et al, 2013;Schlaeppi et al, 2014;Jechalke et al, 2019). However, the relationship between the biotic diversity and biotic resistance towards invading organisms, is not fully understood; it seems that environments with high biological diversity have narrower niches and/or might have a higher chance to harbour natural antagonists and competitors (Chapin III et al, 2000;Loreau and Hector, 2001;Mallon et al, 2015;Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Various databases such as GEO, SalCom, and others (6, 29, 30) were used to identify potential environmental stimuli that induce expression of STM adhesins. However, these analyses only revealed defined culture conditions leading to expression of 3 (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in attachment levels to various salad species were further investigated for S. en terica serovar Typhimurium (STM). Adhesion of STM to lettuce leaves occurred in higher numbers compared to corn salad leaves, moreover persistence in planta was longer for lettuce than for corn salad (6).…”
Section: Introductionmentioning
confidence: 99%
“…S. enterica may adhere to leaves and roots, colonize the plant, and further internalize into the plant tissue. Once inside the plant, S. enterica potentially replicate and persist (7, 8). Endophytic colonization by Salmonella cannot be removed by surface washing, and bacteria will thus be ingested if food is consumed after minimal processing.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the adhesion of S. enterica serovars to various species of salad (7, 1118) with focus on individual adhesion factors. These studies revealed the involvement of flagella and motility as well as further virulence-associated genes in adhesion to salad.…”
Section: Introductionmentioning
confidence: 99%